Clinical implication of NT-proBNP to predict mortality in patients with acute type A aortic dissection: a retrospective cohort study - Rui Zhang; Hao Wang; Chenxi Song; Rui Fu; Kefei Dou; Shuai Liu; Qianqian Liu; Xiaohui Bian; Weida Liu; Chengang Zhu; Jingjing Gao; Sheng Yuan; et al. (BMJ Open)
Objectives Acute type A aortic dissection is a life-threatening cardiovascular disease commonly seen in emergency department, resulting in substantial mortality and morbidity. We aimed to investigate the prognostic value of N-terminal pro-B type natriuretic peptide (NT-proBNP) among this critically ill population.Design The design of this study was a retrospective cohort study.Setting The study population was recruited in the Emergency Department of Fuwai hospital in China from 2018 to 2020.Participants We consecutively enrolled 829 patients with acute type A aortic dissection and measurable baseline NT-proBNP.Primary outcome The primary endpoint was 1-year all-cause death.Results Based on tertiles of NT-proBNP (pg/mL), patients were stratified into low (≤150.3, n=276), intermediate (150.3–667.6, n=277) and high (>667.6, n=276) NT-proBNP groups. Compared with patients with low NT-proBNP, the Kaplan-Meier estimates for primary 1-year mortality were higher in intermediate (32.5% vs 18.1%; HR 1.91, 95% CI 1.35 to 2.69) and high (42.0% vs 18.1%; HR 2.56, 95% CI 1.84 to 3.57) NT-proBNP groups, respectively. After multivariable regression adjusted for confounders, NT-proBNP tertiles were independent predictors for 1-year mortality (adjusted HR for intermediate group 1.52, 95% CI 1.02 to 2.27; adjusted HR for high group 2.17, 95% CI 1.41 to 3.32). Notably, the predictive performance of NT-proBNP for 1-year mortality was greater in patients receiving surgery than conservative treatment (between-cohorts difference in area under the curve 0.13, Delong’s test p=0.04).Conclusion NT-proBNP provides incremental prognostic information for mortality in patients with acute type A aortic dissection who underwent surgical repairment, which could aid in risk stratification as a pragmatic and versatile biomarker in this critically ill population while having limited prognostic value for those receiving conservative treatment.